From Needs Analysis to Programme Design: Online Speaking Skills Upskilling Programme for ESL Teachers - Noraini binti Zulkepli, Intan Safinas binti Mohd Ariff Albakri, Puteri Zarina binti Megat Khalid, Raja Nor Safinas binti Raja Harun (Tanjung Malim, 2024)
From Needs Analysis to Programme Design: Online Speaking Skills Upskilling Programme for ESL Teachers by Noraini binti Zulkepli, Intan Safinas binti Mohd Ariff Albakri, Puteri Zarina binti Megat Khalid, Raja Nor Safinas binti Raja Harun